Issues with Scrum-of-Scrums - Keller, Anne; Rössle, Albin; Sheik, Rami; Thell, Hannes; Westmark, Frida (My University, 2019)
To succeed in the development of products, different approaches can be taken. Two examples of such are the plan-driven method or by using an agile methodology. A commonly used framework within Agile development is Scrum. Within the framework of Scrum there are tools such as Daily Stand-up and Scrum-of-Scrums which are both used for communication. Coordination is critical when it comes to projects involving multiple teams and Scrum-of- Scrums is one possible solution to deal with this. This tool is intended to focus on team communication and is used for inter-team coordination. It is used in an up-scaled context, where the Daily Stand-up meeting is not suitable, but does not work nearly as well. As prob- lems with Scrum-of-Scrums are identified there is an interest in finding out what separates Daily Stand-ups from Scrum-of-Scrums and what makes the latter less successful. First, a pre-study was conducted to define a purpose of the study. When the purpose had been defined, the appropriate methods for the study was decided upon. It was decided to conduct a literature review and to find empirical data by the use of semi-structured interviews. The interviews were held with respondents working with the concepts Daily Stand-up and Scrum-of-Scrums. The literature review and semi-structured interviews were conducted simultaneously, to meet the set purpose. The result showed a variance when it came to how to implement both Daily Stand-up as well as Scrum-of-Scrums. It was found that the respondents had a broader common under- standing on how to implement and use the Daily Stand-up meetings than they had when it came to the implementation of the Scrum-of-Scrums meeting. Among the respondents there was a difference to be found when it came to the length of the meeting as well as which topics being discussed during the meeting. There was also a difference in who is attending the meeting. In some cases the Scrum Master was sent to the meeting and in others the Product Owner or a team member was sent to represent the group. It was found that one of the biggest issues when implementing the Scrum-of-Scrums meeting was the lack of interest which was caused by the meeting not having a clear purpose. To lastly conclude the findings from the result, it was found that there is no easy way to use the Scrum-of-Scrums meeting. It is not as straight forward as implementing the Daily Stand-up meeting. This does not mean that Scrum-of-Scrums is outdated or that it is a less useful tool, but rather that it does not offer a solution for all cases of coordination.